Comparison of the ability of pyridinium aldoximes to reactivate human red blood cell acetylcholinesterases inhibited by ethyl- and methyl-paraoxon - Petroianu, Georg; Lorke, Dietrich E.; Kaláscz, Huba (Current organic chemistry, 2012)
Oximes are acetylcholinesterase reactivators of use in poisoning with organophosphorus inhibitors of cholinesterase (OPIChE: (organophosphates and organophosphonates). They are clinically used as an adjunct to atropine in such exposure. Clinical experience with oximes is, however, disappointing. This paper reviews available data concerning the ability of established and new oximes to reactivate cholinesterases inhibited by two differently substituted prototypical organophosphates: ethyl- and methyl-paraoxon. The intrinsic toxicity of oximes is quantified in vitro by measuring the concentration required to inhibit red blood cell (RBC) cholinesterase activity by 50% (IC50). Reactivation ability is assessed in vitro via the IC50 shift graph. The slope of the shift graph (tan α) is used to quantify the magnitude of the protective effect (nM IC50 increase per µM reactivator). The ranking of reactivating potencies of the examined oximes determined with methyl-paraoxon as an inhibitor is essentially the same as the ranking obtained using ethyl-paraoxon as an inhibitor. In the in vitro model used, the presence of ethyl versus methyl substituents does not seem to significantly alter the ability of the examined oximes to reactivate the esterase. In vitro derived results were subsequently validated in vivo in rats using ethyl-paraoxon and methyl-paraoxon as cholinesterase inhibitors and various oximes as reactivators. Mortality data were compared and hazard ratios calculated using Cox proportional hazards model. Overall, the ability of in vitro testing (tan α determinations) to predict in vivo protection by oximes is limited.